Flexible neutron protection material and preparation method thereof
By introducing boron elements into the silicone resin matrix, a flexible neutron protection material was prepared, which solved the problems of large weight and poor flexibility of traditional neutron protection materials, and achieved excellent heat resistance, mechanical properties and neutron protection. ability.
Patent Information
- Application Number
- CN202411672633.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to problems such as large weight, poor flexibility, and difficult processing, traditional neutron protection materials are difficult to meet the needs of lightweight and efficient neutron protection materials in the fields of aerospace, nuclear industry and medical care.
A flexible neutron protective material is prepared by introducing boron elements into the silicone resin matrix. The specific method is to stir and mix alkoxysilane, phenylboric acid and diphenyldihydrocarbylboric acid, and then react dropwise with the boric acid solution to obtain a hydrolytic crosslinking solution, and then obtain a boron-modified silicone resin by decompression distillation, and Mixed with a curing agent and an organic solvent, apply it to the surface of the substrate to cure.
The material has a thermal weight loss rate of less than 10% after heating at 500°C for 1 hour. It has excellent heat resistance and mechanical properties. At the same time, its Young's modulus is low, showing good flexibility and low internal stress, which can be effective The durability of the material is improved, and the sub-shielding capacity exceeds 25%, showing a high neutron protection effect.
Smart Images

Figure BDA0005146254690000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic polymer materials, and in particular to a flexible neutron shielding material and a preparation method thereof. Background Art
[0002] Neutron radiation protection is an important topic in the field of nuclear energy utilization and nuclear safety. Traditional neutron protection materials usually use high-density metals or hydrogen-containing compounds. Although these materials have certain neutron shielding capabilities, they often have problems such as heavy weight, poor flexibility, and difficult processing, which limits their use in certain applications. With the development of science and technology, especially in the fields of aerospace, nuclear industry, and medicine, the demand for lightweight and efficient neutron protection materials is increasing.
[0003] In recent years, flexible neutron shielding materials have attracted extensive attention due to their light weight, easy processing and good adaptability. Such materials usually achieve neutron shielding effects by introducing boron-containing compounds into a polymer matrix. Boron has a high neutron absorption cross section and is an ideal neutron absorber. The neutron absorption capacity is positively correlated with the amount of boron added. However, a high content of boron may cause the mechanical properties of the material to deteriorate, especially in high temperature environments. The heat resistance and mechanical properties of the material may not meet the requirements of practical applications. Summary of the invention
[0004] In view of this, the object of the present invention is to propose a flexible neutron shielding material and a preparation method thereof, so as to provide a flexible material with excellent mechanical properties, heat resistance and neutron shielding capabilities.
[0005] Based on the above purpose, the present invention provides a flexible neutron shielding material, which is obtained by mixing a boron silicone resin and a curing agent in an organic solvent, applying the mixture on a substrate surface, and curing the mixture.
[0006] Furthermore, the weight ratio of the boron silicone resin, the curing agent and the organic solvent is 80-120:3-7:30-80.
[0007] Furthermore, the preparation method of the boron organosilicon resin is as follows:
[0008] (1) mixing alkoxysilane, phenylboric acid and diphenyldialkylboric acid, heating to 75-85° C. to obtain a mixed solution, then dissolving the boric acid in deionized water, adding the solution dropwise to the mixed solution, stirring and reacting for 2-4 hours to obtain a hydrolyzed cross-linking solution;
[0009] (2) The hydrolyzed cross-linked solution is subjected to reduced pressure distillation to obtain a boron-modified silicone resin.
[0010] Furthermore, in step (1), the alkoxysilane is one or a mixture of methyltriethoxysilane, propyltriethoxysilane, dimethyldiethoxysilane and phenyltriethoxysilane.
[0011] Preferably, the alkoxysilane is propyltriethoxysilane, dimethyldiethoxysilane and phenyltriethoxysilane in a weight ratio of 7:2:1.
[0012] Furthermore, in the step (1), the weight ratio of alkoxysilane, phenylboric acid, diphenyldialkylboric acid, boric acid and deionized water is 80-120:5-15:0.5-2:8-12:40-60.
[0013] Preferably, the curing agent is one of n-butyl titanate, isopropyl titanate and isooctyl titanate.
[0014] Preferably, the organic solvent is one of n-butanol, isobutanol, n-propanol and isopropanol.
[0015] Preferably, the vacuum degree of the reduced pressure distillation in step (2) is 0.075-0.085 MPa, the temperature is 105-115° C., and the time is 6-8 h.
[0016] Preferably, the thickness of the flexible neutron shielding material is 0.5-2 mm.
[0017] Furthermore, the present invention also provides a method for preparing a flexible neutron shielding material, comprising the following steps: adding a boron silicone resin and a curing agent into an organic solvent, stirring for 20-40 minutes, and then applying the mixture on the surface of a substrate and curing the mixture to obtain a flexible neutron shielding material.
[0018] Preferably, the curing is carried out by placing the mixture at room temperature for 10-14 hours, then heating the mixture to 100-110° C. and placing the mixture for 2-4 hours.
[0019] Beneficial effects of the present invention:
[0020] The flexible neutron protection material prepared by the present invention has excellent mechanical properties, heat resistance and neutron protection capabilities. The thermal weight loss rate of the material after heating at 500°C for 1 hour is less than 10%, indicating that it has excellent heat resistance. At the same time, the Young's modulus of the material under 300% tensile strain is low, showing good flexibility and low internal stress, which can avoid cohesive failure caused by excessive internal stress, thereby improving the durability of the material and will not break even after multiple stretching. In addition, when the material is used as a neutron protection material, its shielding capacity exceeds 25%, showing a high neutron protection effect.
[0021] The addition of phenylboronic acid and diphenylboronic acid plays a key role in the flexibility and heat resistance of the material. Phenylboronic acid and diphenylboronic acid avoid the problem of excessive crosslinking density caused by adding boric acid alone by regulating the crosslinking density of the material. Phenylboronic acid contains two boron hydroxyl sites, while diphenylboronic acid contains one boron hydroxyl site. These sites work synergistically to optimize the molecular chain crosslinking density of the material. In addition, the introduction of phenyl further improves the heat resistance of the material.
[0022] In summary, the present invention successfully prepares a flexible material with excellent mechanical properties, heat resistance and neutron protection capabilities by precisely controlling the chemical composition and cross-linking structure of the material, providing a new solution for the field of neutron protection. DETAILED DESCRIPTION
[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0024] Embodiment 1:
[0025] (1) 60 g of methyltriethoxysilane, 20 g of dimethyldiethoxysilane, 5 g of phenylboric acid and 0.5 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 75° C. to obtain a mixed solution, and then 8 g of boric acid was dissolved in 40 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 2 h to obtain a hydrolyzed cross-linking solution;
[0026] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.0875 MPa, a temperature of 105° C., and a time of 6 h to obtain a boron-modified silicone resin;
[0027] (3) 80 g of boron silicone resin and 3 g of n-butyl titanate were added to 30 g of n-butanol, stirred for 20 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 10 h, and then heated to 100 ° C and placed for 2 h to obtain a flexible neutron shielding material with a thickness of 1 mm.
[0028] Embodiment 2:
[0029] (1) 70 g of propyltriethoxysilane, 20 g of dimethyldiethoxysilane, 10 g of phenyltriethoxysilane, 10 g of phenylboric acid and 1 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 80° C. to obtain a mixed solution, and then 10 g of boric acid was dissolved in 50 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 3 h to obtain a hydrolyzed cross-linking solution;
[0030] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.08 MPa, a temperature of 110° C., and a time of 7.5 h to obtain a boron-modified silicone resin;
[0031] (3) 100 g of boron silicone resin and 5 g of n-butyl titanate were added to 50 g of n-butanol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 12 h, and then heated to 110° C. and placed for 3 h to obtain a flexible neutron shielding material with a thickness of 1 mm.
[0032] Embodiment 3:
[0033] (1) 80 g of propyltriethoxysilane, 40 g of dimethyldiethoxysilane, 15 g of phenylboric acid and 2 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 85° C. to obtain a mixed solution, and then 12 g of boric acid was dissolved in 60 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 4 hours to obtain a hydrolysis cross-linking solution;
[0034] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.085 MPa, a temperature of 115° C., and a time of 8 h to obtain a boron-modified silicone resin;
[0035] (3) 120 g of boron organic silicone resin and 7 g of n-butyl titanate were added to 80 g of n-propanol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 14 h, and then heated to 115° C. and placed for 4 h to obtain a flexible neutron shielding material with a thickness of 1 mm.
[0036] Embodiment 4:
[0037] (1) 80 g of propyltriethoxysilane, 20 g of phenyltriethoxysilane, 10 g of phenylboric acid and 1 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 80° C. to obtain a mixed solution, and then 10 g of boric acid was dissolved in 60 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 3 h to obtain a hydrolysis cross-linking solution;
[0038] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.08 MPa, a temperature of 110° C., and a time of 7.5 h to obtain a boron-modified silicone resin;
[0039] (3) 100 g of boron silicone resin and 5 g of n-butyl titanate were added to 50 g of isobutyl alcohol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 12 h, and then heated to 105° C. and placed for 3 h to obtain a flexible neutron shielding material with a thickness of 1 mm.
[0040] Comparative Example 1:
[0041] The difference between Comparative Example 1 and Example 2 is that the phenylboric acid in step (1) is replaced by an equimolar amount of boric acid;
[0042] The specific steps are as follows:
[0043] (1) 70 g of propyltriethoxysilane, 20 g of dimethyldiethoxysilane, 10 g of phenyltriethoxysilane and 1 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 80° C. to obtain a mixed solution, and then 15 g of boric acid was dissolved in 50 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 3 h to obtain a hydrolysis cross-linking solution;
[0044] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.08 MPa, a temperature of 110° C., and a time of 7.5 h to obtain a boron-modified silicone resin;
[0045] (3) 100 g of boron silicone resin and 5 g of n-butyl titanate were added to 50 g of n-butanol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 12 h, and then heated to 110° C. and placed for 3 h to obtain a protective material with a thickness of 1 mm.
[0046] Comparative Example 2:
[0047] The difference between Comparative Example 2 and Example 2 is that the diphenyldialkylboric acid in step (1) is replaced by an equimolar amount of boric acid;
[0048] The specific steps are as follows:
[0049] (1) 70 g of propyltriethoxysilane, 20 g of dimethyldiethoxysilane, 10 g of phenyltriethoxysilane and 10 g of phenylboric acid were stirred and mixed, and the temperature was raised to 80° C. to obtain a mixed solution, and then 10.34 g of boric acid was dissolved in 50 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 3 h to obtain a hydrolysis cross-linking solution;
[0050] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.08 MPa, a temperature of 110° C., and a time of 7.5 h to obtain a boron-modified silicone resin;
[0051] (3) 100 g of boron silicone resin and 5 g of n-butyl titanate were added to 50 g of n-butanol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 12 h, and then heated to 110° C. and placed for 3 h to obtain a protective material with a thickness of 1 mm.
[0052] Comparative Example 3:
[0053] The difference between Comparative Example 3 and Example 2 is that: in step (1), the amount of phenylboric acid added is 1 g, and the amount of diphenyldialkylboric acid added is 10 g;
[0054] The specific steps are as follows:
[0055] (1) 70 g of propyltriethoxysilane, 20 g of dimethyldiethoxysilane, 10 g of phenyltriethoxysilane, 1 g of phenylboric acid and 10 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 80° C. to obtain a mixed solution, and then 10 g of boric acid was dissolved in 50 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 3 h to obtain a hydrolyzed cross-linking solution;
[0056] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.08 MPa, a temperature of 110° C., and a time of 7.5 h to obtain a boron-modified silicone resin;
[0057] (3) 100 g of boron silicone resin and 5 g of n-butyl titanate were added to 50 g of n-butanol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 12 h, and then heated to 110° C. and placed for 3 h to obtain a protective material with a thickness of 1 mm.
[0058] Comparative Example 4:
[0059] The difference between Comparative Example 4 and Example 2 is that: the amount of deionized water added in step (1) is 100 g;
[0060] The specific steps are as follows:
[0061] (1) 70 g of propyltriethoxysilane, 20 g of dimethyldiethoxysilane, 10 g of phenyltriethoxysilane, 10 g of phenylboric acid and 1 g of diphenyldialkylboric acid were stirred and mixed, and the temperature was raised to 80° C. to obtain a mixed solution, and then 10 g of boric acid was dissolved in 100 g of deionized water, and the mixture was added dropwise to the mixed solution, and the mixture was stirred for reaction for 3 h to obtain a hydrolysis cross-linking solution;
[0062] (2) subjecting the hydrolyzed cross-linking solution to reduced pressure distillation at a vacuum degree of 0.08 MPa, a temperature of 110° C., and a time of 7.5 h to obtain a boron-modified silicone resin;
[0063] (3) 100 g of boron silicone resin and 5 g of n-butyl titanate were added to 50 g of n-butanol, stirred for 30 min, and then applied to the surface of the substrate. The mixture was placed at room temperature for 12 h, and then heated to 110° C. and placed for 3 h to obtain a protective material with a thickness of 1 mm.
[0064] Performance Testing:
[0065] Mechanical properties: At room temperature, the tensile strength and elongation at break were tested according to standard GB / T528-1998. A universal tensile machine was used to test the mechanical properties of dumbbell-shaped specimens with a length of 11.5 cm and a thickness of 2 mm. The tensile speed was 100 mm / min. Each sample was measured three times and the average value of the data was taken. The Young's modulus at 300% tensile strain was calculated. The results are shown in Table 1.
[0066] Heat resistance: The protective materials prepared in the examples and comparative examples were gradually heated in a muffle furnace at a heating rate of 10°C / min. After continuous heating at 500°C for 1 hour, the temperature was slowly lowered to room temperature. After constant weight, the thermal weight loss rate of the protective materials prepared in the examples and comparative examples was measured by differential gravimetry. The results are shown in Table 1.
[0067] Neutron protection performance: The protective materials prepared in the embodiments and comparative examples were used to construct a hollow spherical shielding body with an inner diameter of 5 cm and an outer diameter of 6 cm (i.e., the thickness of the shielding body was 1 cm), and an isotropic neutron and gamma-ray point source. The neutron flux of the 252Cf point neutron source was 1×10 9 n / cm 2 , the source term is located at the geometric center of the model, the neutron flux at a distance of 5 cm from the protective material is measured, and the attenuation ratio is calculated. The results are shown in Table 1.
[0068] Table 1 Performance test results
[0069]
[0070] Data Analysis:
[0071] From the data of Examples 1-4, it can be seen that the flexible neutron protection material prepared by the present invention has high tensile strength and elongation at break. After heating at 500°C for 1 hour, its thermal weight loss rate is less than 10%, indicating that it has excellent mechanical properties and heat resistance. In addition, the Young's modulus of 300% tensile strain is low, indicating that it has excellent flexibility, small internal stress, and can avoid cohesive failure caused by excessive internal stress. It has strong durability and will not break after multiple stretching. Most importantly, when it is used as a neutron protection material, its shielding is above 25%, indicating that it has a high neutron protection capability.
[0072] It can be seen from the data of Example 2 and Comparative Examples 1-2 that the addition of phenylboric acid and diphenyldialkylboric acid helps to improve the flexibility and heat resistance of the protective material. This is mainly because phenylboric acid and diphenyldialkylboric acid regulate the crosslinking density of the protective material. Phenylboric acid contains two boron hydroxyl sites, and diphenyldialkylboric acid contains one boron hydroxyl site, which synergistically regulate the crosslinking density of the molecular chains in the protective material with the three boron hydroxyl sites, avoiding the problem of excessive crosslinking density caused by adding boric acid alone. In addition, the phenyl group introduced by phenylboric acid and diphenyldialkylboric acid helps to further improve the heat resistance, which is mainly due to the rigidity of benzene itself and the protection of small groups on the silicone molecules.
[0073] It can be seen from the data of Example 2 and Comparative Example 3 that the usage ratio of phenylboric acid and diphenyldialkylboric acid has a significant effect on improving the flexibility and heat resistance of the protective material, which further proves the regulatory effect of phenylboric acid and diphenyldialkylboric acid.
[0074] It can be seen from the data of Example 2 and Comparative Example 4 that the amount of deionized water added has a significant effect on the flexibility and heat resistance of the protective material. This is because when the amount of deionized water added is too high, it will cause excessive hydrolysis of siloxane, resulting in excessive crosslinking density and decreased crosslinking uniformity.
[0075] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A flexible neutron shielding material, characterized in that: The boron silicone resin and the curing agent are mixed in an organic solvent, applied to the surface of the substrate, and cured to obtain; The weight ratio of the boron organosilicon resin, the curing agent and the organic solvent is 80-120:3-7:30-80; The preparation method of the boron organosilicon resin is as follows: (1) mixing alkoxysilane, phenylboric acid and diphenyldialkylboric acid, heating to 75-85° C. to obtain a mixed solution, then dissolving the boric acid in deionized water, adding the solution dropwise to the mixed solution, stirring and reacting for 2-4 hours to obtain a hydrolyzed cross-linking solution; (2) performing reduced pressure distillation on the hydrolyzed cross-linked solution to obtain a boron-modified silicone resin; In step (1), the alkoxysilane is one or a mixture of methyltriethoxysilane, propyltriethoxysilane, dimethyldiethoxysilane and phenyltriethoxysilane; In the step (1), the weight ratio of alkoxysilane, phenylboric acid, diphenyldialkylboric acid, boric acid and deionized water is 80-120:5-15:0.5-2:8-12:40-60.
2. The flexible neutron shielding material according to claim 1, characterized in that: The curing agent is one of n-butyl titanate, isopropyl titanate and isooctyl titanate.
3. The flexible neutron shielding material according to claim 1, characterized in that: The organic solvent is one of n-butanol, isobutanol, n-propanol and isopropanol.
4. The flexible neutron shielding material according to claim 1, characterized in that: The alkoxysilane is propyltriethoxysilane, dimethyldiethoxysilane and phenyltriethoxysilane in a weight ratio of 7:2:
1.
5. The flexible neutron shielding material according to claim 1, characterized in that: The vacuum degree of the reduced pressure distillation in step (2) is 0.075-0.085 MPa, the temperature is 105-115° C., and the time is 6-8 h.
6. The flexible neutron shielding material according to claim 1, characterized in that: The thickness of the flexible neutron protection material is 0.5-2 mm.
7. A method for preparing the flexible neutron shielding material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: adding boron organic silicon resin and curing agent into an organic solvent, stirring for 20-40 minutes, and then brushing on the surface of a substrate and curing to obtain a flexible neutron protection material.
8. The method for preparing the flexible neutron shielding material according to claim 7, characterized in that: The curing is carried out by placing the mixture at room temperature for 10-14 hours, then heating the mixture to 100-110° C. and placing the mixture for 2-4 hours.